Forward-looking planning of technology development - Halicka, Katarzyna (Business, Management and Economics Engineering, 2015)
The main aim of this article is to adapt the Future-Oriented Technology Analysis (FTA) to prospective planning of technology development. Firstly, the article presents the assumptions, methods and idea, as well as the concept of the FTA method. Moreover, selected publications on the use of this method were analysed. Then, an original, base model of forward-looking planning of technology development was constructed and presented. The end result of this process will be the development of the localized in time, presented in graphic form, action plan referred to as the route of technology development. Basing on the literature review and the research projects a preliminary route of development of arbitrarily chosen technology was also built and presented.